2016
DOI: 10.1093/eurheartj/ehw132
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of finerenone vs. eplerenone in patients with worsening chronic heart failure and diabetes mellitus and/or chronic kidney disease

Abstract: AimsTo evaluate oral doses of the non-steroidal mineralocorticoid receptor antagonist finerenone given for 90 days in patients with worsening heart failure and reduced ejection fraction and chronic kidney disease and/or diabetes mellitus.Methods and resultsMiner Alocorticoid Receptor antagonist Tolerability Study-Heart Failure (ARTS-HF) was a randomized, double-blind, phase 2b multicentre study (ClinicalTrials.gov: NCT01807221). Of 1286 screened patients, 1066 were randomized. Patients received oral, once-dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
254
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 338 publications
(275 citation statements)
references
References 35 publications
3
254
1
17
Order By: Relevance
“…14 Furthermore, the international phase 2b trial ARTSHeart Failure (ARTS-HF) in patients with worsening CHF and T2DM and/or CKD showed that finerenone was well tolerated and the proportion of patients with a decrease in N-terminal pro-BNP (NT-proBNP) of 30% from baseline to day 90 was similar in the finerenone groups to that in the eplerenone group. 15 The international phase 2b ARTS-Diabetic Nephropathy (ARTS-DN) conducted in patients with diabetic kidney disease showed that finerenone therapy led to improvements in the urinary-albumin-creatinine ratio, with a similar safety profile as placebo. 16 Based on the international ARTS-HF, the ARTS-HF Japan (Clinicaltrials.gov Identifier: NCT01955694) was designed to investigate the safety and efficacy of 5 treatment regimens of once-daily (o.d.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Furthermore, the international phase 2b trial ARTSHeart Failure (ARTS-HF) in patients with worsening CHF and T2DM and/or CKD showed that finerenone was well tolerated and the proportion of patients with a decrease in N-terminal pro-BNP (NT-proBNP) of 30% from baseline to day 90 was similar in the finerenone groups to that in the eplerenone group. 15 The international phase 2b ARTS-Diabetic Nephropathy (ARTS-DN) conducted in patients with diabetic kidney disease showed that finerenone therapy led to improvements in the urinary-albumin-creatinine ratio, with a similar safety profile as placebo. 16 Based on the international ARTS-HF, the ARTS-HF Japan (Clinicaltrials.gov Identifier: NCT01955694) was designed to investigate the safety and efficacy of 5 treatment regimens of once-daily (o.d.)…”
Section: Discussionmentioning
confidence: 99%
“…The design of ARTS-HF Japan is based on that of the international ARTS-HF, which was the first clinical trial to investigate the novel nonsteroidal MRA finerenone in comparison with eplerenone in patients with worsening HFrEF requiring emergency treatment and who also had T2DM and/or CKD. 15 This will allow data from the 2 studies to be pooled for further analyses.…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…MRAs also reduce albuminuria and have additional cardiovascular benefits (107)(108)(109)(110) (112). A Cochrane systematic review did not find conclusive evidence for or against blood pressure treatment for mild to moderate preexisting hypertension to reduce the risk of preeclampsia, preterm birth, small-for-gestational-age infants, or fetal death (113).…”
Section: Resistant Hypertensionmentioning
confidence: 99%
“…diuretics. The reason for this choice is that the incidence rate of HF hospitalizations has decreased over the years due to advances in the treatment of HF, and the fact that there are geographic differences in the treatment of HF and the definition of hospitalization that led to different rates of HF hospitalization 34, 35, 36. The broader definition is intended to ensure that the event rate is high enough to have an achievable sample size and to accommodate geographic differences due to differing health care systems.…”
Section: Discussionmentioning
confidence: 99%